A novel method based on thermal conductivity for material identification in scrap industry: An experimental validation. (October 2018) - Cuce, Erdem; Cuce, Pinar Mert; Guclu, Tamer; Besir, Ahmet; Gokce, Erkan; Serencam, Ugur
Highlights: A novel method based on thermal conductivity for sorting of metals is developed. The accuracy of the method is justified through copper, stainless steel and brass. k-Value of copper, stainless steel and brass is found to be 397.37, 44.92 and 114.67 W/mK, respectively. Errors in the said measurements are calculated to be 1.37, 4.46 and 3.31%, respectively. The results are in very good accordance with the manufacturers' data reports. Abstract: Fast, accurate and reliable identification and sorting of materials is still a challenge in recycling sector. Scrap metals are often classified through density and colour, which cause notable financial burdens to the companies in most cases. Within the scope of this research, a novel method based on thermal conductivity is presented for material identification in scrap industry. The unit consists of a constant heat flux source and a cooling system, in which axial heat conduction is enabled and radial heat transfer is eliminated. For the steady-state conditions, temperature gradient across the sample metals is measured along with the constant heat flux value, and the thermal conductivity of the samples is determined via the Fourier's heat conduction law. Copper, brass and stainless steel samples are considered in this research to verify the accuracy of the results. For a reliable and scientific approach, three independent sets of experiments are conducted, and the results are evaluated in terms of accuracy and consistency. Experimental thermal conductivity values of the said samples are compared with the reported data in literature and a good accordance is achieved. Error in measurements is calculated to be 1.37, 3.31 and 4.46% for copper, brass and stainless steel sample, respectively which is acceptable. The tests are repeated with highly sensitive probes for aluminium sample, and the measurement error is calculated to be 0.56%.